A meta‐analysis of experimental warming effects on terrestrial nitrogen pools and dynamics. Issue 2 (4th April 2013) - Bai, Edith; Li, Shanlong; Xu, Wenhua; Li, Wei; Dai, Weiwei; Jiang, Ping
Summary: Global warming may have profound effects on terrestrial ecosystems. However, a comprehensive evaluation of the effects of warming on ecosystem nitrogen (N) pools and dynamics is not available. Here, we compiled data of 528 observations from 51 papers and carried out a meta‐analysis of experimental warming effects on 13 variables related to terrestrial N pools and dynamics. We found that, on average, net N mineralization and net nitrification rate were increased by 52.2 and 32.2%, respectively, under experimental warming treatment. N pools were also increased by warming, although the magnitude of this increase was less than that of N fluxes. Soil microbial N and N immobilization were not changed by warming, probably because microbes are limited by carbon sources. Grassland and shrubland/heathland were less responsive to warming than forest, probably because the reduction of soil moisture by warming offset the temperature effect in these areas. Soil heating cable and all‐day treatment appeared to be the most effective method on N cycling among all treatment methods. Results of this meta‐analysis are useful for better understanding the response of N cycling to global warming and the underlying mechanism of warming effects on plants and ecosystem functions.